High-stakes testing and student achievement: Updated analyses with NAEP data - Nichols, Sharon; Glass, Gene; Berliner, David (Education Policy Analysis Archives, 2012)
The present research is a follow-up study of earlier published analyses that looked at the relationship between high-stakes testing pressure and student achievement in 25 states. Using the previously derived Accountability Pressure Index (APR) as a measure of state-level policy pressure for performance on standardized tests, a series of correlation analyses was conducted to explore relationships between high-stakes testing accountability pressure and student achievement as measured by the National Assessment for Education Progress (NAEP) in reading and math. Consistent with earlier work, stronger positive correlations between the pressure index and NAEP performance in fourth grade math and weaker connections between pressure and fourth and eighth grade reading performance were found. Policy implications and future directions for research are discussed.